2018
DOI: 10.1186/s12951-018-0373-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interneurons required for the aversive response of Caenorhabditis elegans to graphene oxide

Abstract: BackgroundSo far, how the animals evade the environmental nanomaterials is still largely unclear. In this study, we employed in vivo assay system of Caenorhabditis elegans to investigate the aversive behavior of nematodes to graphene oxide (GO) and the underlying neuronal basis.ResultsIn this assay model, we detected the significant aversive behavior of nematodes to GO at concentrations more than 50 mg/L. Loss-of-function mutation of nlg-1 encoding a neuroligin with the function in connecting pre- and post-syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 51 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…Acute treatment did not result in any defects in the measured phenotypes but, curiously, we detected a mobility increase. This trait could be an aversion response, or fight‐and‐flight response, similarly observed upon exposure to pathogenic bacteria, indicating that worms can sense GO material . The C. elegans intestine acts as a barrier to environmental toxins, metals, nanomaterials or pathogens, and it is instrumental for implementing a systemic innate immune response .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Acute treatment did not result in any defects in the measured phenotypes but, curiously, we detected a mobility increase. This trait could be an aversion response, or fight‐and‐flight response, similarly observed upon exposure to pathogenic bacteria, indicating that worms can sense GO material . The C. elegans intestine acts as a barrier to environmental toxins, metals, nanomaterials or pathogens, and it is instrumental for implementing a systemic innate immune response .…”
Section: Resultssupporting
confidence: 89%
“…This trait could be an aversion response, or fight-and-flight response, similarly observed upon exposure to pathogenic bacteria, [70] indicating that worms can sense GO material. [71] The C. elegans intestine acts as a barrier to environmental toxins, metals, nanomaterials or pathogens, [46,65,72] and it is instrumental for implementing a systemic innate immune response. [73] Our genome-wide RNA-Seq data of acutely GO-treated animals showed an induced expression of innate immune response genes, which significantly, albeit mildly positive correlated with gene expression data obtained from C. elegans that encountered pathogenic PA14 bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Graphite, GQDs, and especially GO nanoplatelets induced behavioral deficits and damages in dopaminergic and glutamatergic neurons in nematode Caenorhabditis elegans , and several antimicrobial proteins related to insulin signaling pathways were found to be activated . Similarly, GO undertaken by zebrafish could be transferred to the offspring brain, resulting in more predominant neurotoxicity in the offspring than in the parental zebrafish .…”
Section: Biocompatibilities and Toxicities Of Graphene‐family Nanomatmentioning
confidence: 99%
“…Despite being a relatively novel material, evidence has demonstrated the cytotoxicity of GO NPs on various types of cells via a number of mechanisms, such as membrane damage, ROS generation, and expression level alterations of several key genes related to apoptosis [107]. Adverse eff ects against non-mammalian were also determined, and toxicity against Caenorhabditis elegans (C. elegans), a representative of roundworms, has primarily been studied [108][109][110][111][112]. Th ese studies showed impaired functions in the intestine, neurons and reproductive organs upon exposure to GO NPs, which were ascribed to a weakened epidermal barrier as a consequence of peroxidase formation in the epidermis.…”
Section: Non-metalsmentioning
confidence: 99%